Penan Arts & Crafts - Faridah, Sahari (sarawak Energy Bhd, 2022)
The Penan are renowned for their fine arts and craft-making ability, and they have made an immense contribution to Sarawak culture (Langub, 1991). Each of their produced artefact is adorned with beautiful designs and unique styles carrying distinctive indigenous motifs. These artefacts are produced for many reasons: trade, daily use, ritual and ceremonial purposes (Chin, 1980). Their talents are apparent in their variety of craft products which includes Malat, rattan baskets and rattan mats. For centuries, the Penan’s art and crafts have benefited from the availability of rich and diverse natural resources. They have creatively harnessed the readily available natural raw materials through the rich interactions with their surroundings. The vast selection of rattan varieties were formerly the most preferred raw material used (Chin, 1985, Brosius, 1986).